Kedudukan Al-Quran Dan Hadis Sebagai Dasar Pendidikan Islam - Hoirul Anam; Mochamad Aris Yusuf; Siti Saada (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2022)
Â Islamic education, is a very urgent thing in a life for all mankind. This is because Islamic education is a means for all humans, in order to achieve their life goals, namely to get happiness in the world and in the hereafter. The basis of Islamic education which is the main reference there are two things, namely the Qur'an and hadith. So the article written by the author wants to reveal the position of the Qur'an and hadith for Islamic education. The research method used by the author uses literature study research, which is a series of activities carried out by the author regarding the data collection method that focuses on the bibliography, by reading, taking notes and then managing the necessary data. So with this method it can dismantle the position of the Qur'an and hadith as the basis of Islamic education. The results of this study indicate that the position of the Qur'an and hadith in Islamic education has similarities between the two, namely both being the main reference in Islamic education, but both also have differences. Because if the Qur'an is a global revelation. So to understand it requires interpretation. While the hadith serves to provide an explanation of the concepts contained in the Qur'an including education, as well as being an example as a role model.